Descriptive Analytics Sales Data Visualization at Kebab Made Using Google Data Studio - Riani, Ni Komang Indah Candrika; Wiguna, Komang Arya Ganda; Parwita, Wayan Gede Suka; Ratnaningrum , Luh Putu Rara Ayu (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
Kebab Made is a company engaged in the sale of food. It applies an information system in recording and managing data that produces operational information, including sales reports were presented in tabular form. The report cannot display the information about sales growth. The difference in product sales comparison is a weakness of the report results. Thus, another application is needed to reprocess tabulated data into information in the form of graphs. In this study, a system was built using website-based google data studio tools to assist companies in processing tabulated data into a graphs that do not require a long time. The research method used in this research is Kimball's Nine Steps method and conducted through the stages of functional requirements analysis, data warehouse design, Extract Transform Load (ETL) process, system implementation, and system testing. The system was tested using User Acceptance Test (UAT), and showed that the system had run according to the needs. The result of this research is a dashboard that displays information in graphical form to assist in decision making. This visualization allows companies to easily see and analyze sales developments, so they can make more precise and quick decisions.